Intracranial haemorrhage in children and adolescents with severe haemophilia A or B – the impact of prophylactic treatment. (12th July 2017) - Andersson, Nadine G.; Auerswald, Günter; Barnes, Chris; Carcao, Manuel; Dunn, Amy L.; Fijnvandraat, Karin; Hoffmann, Marianne; Kavakli, Kaan; Kenet, Gili; Kobelt, Rainer; Kurnik, Karin; Liesner, Ri; et al.
Summary: The discussion of prophylactic therapy in haemophilia is largely focused on joint outcomes. The impact of prophylactic therapy on intracranial haemorrhage (ICH) is less known. This study aimed to analyse ICH in children with haemophilia, with a focus on different prophylaxis regimens and sequelae of ICH. We conducted a multicentre retrospective and prospective study that included 33 haemophilia centres from 20 countries. Inclusion criteria were children and adolescents born between 1993 and 2014, with severe haemophilia A or B without inhibitors. Participants were categorized by prophylaxis regimen: full, partial or none, based on dose and dose frequency of regular infusions. The cohort study included 1515 children: 29 cases of ICH over 8038 patient years were reported. The incidence of ICH in the prophylaxis group, 0·00033 cases of ICH/patient year, was significantly lower compared to the no prophylaxis group, 0·017 cases of ICH/patient year (RR 50·06; P < 0·001) and the partial prophylaxis group, 0·0050 cases of ICH/patient year (RR 14·92; P = 0·007). In the on‐demand‐group, 8% (2/24) children with ICH died and 33% had long‐term sequelae, including intellectual and behavioural problems, paresis and epilepsy. Children on regular, frequent prophylaxis have a low risk of ICH compared to those using non‐frequent or no prophylaxis.